South-facing exterior wall of the Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the south-facing exterior wall of the Shiva Temple. All the wall projections are adorned with sculptures. The bhadra (central projection) has a sculpture of Tripurantaka Shiva, the intermediate projections have surasundaris (celestial damsels), and the corner projections have dikpalas (deities for cardinal directions). The jangha (wall) portion of the temple is in a different stone than the rest of the temple. The projections are separated by recesses, except for one recess between the wall of the shrine and the mandapa (pillared hall).